Pengaruh Penggunaan Telepon Seluler Terhadap Hasil Balajar Mahasiswa pada Program Studi S1 Pendidikan Ekonomi Angakatan 2015 Fakultas Ekonomi Universitas Negeri Gorontalo - Maryam Ilato; Muhammad Amir Arham; Boby R. Payu (Jambura Economic Education Journal, 2019)
This research aims at investigating in what extent the influence of mobile phone utilization towords students learningachievement in bachelor study Program of Economics, Batchof 2015, Faculty of Economics, State University of Gorontalo.It applies quantitative method. Techniques of date collectionare observation, questionnaire, and documentation and Technique of date analysis is simple linear regression. Samples are 42 students. Finding reveals that mobile phone positively influences learning achievement students of Dapartement of Economics, State of University of Gorontalo. Thehigher the frequency of students in using mobile phone inlearning process leads to tower their learning achievement.